Systematic review and meta-analysis of isolated posterior fossa malformations on prenatal imaging (part 2): neurodevelopmental outcome - D'Antonio, FD; Khalil, A; Garel, C; Pilu, G; Rizzo, G; Lerman-Sagie, T; Bhide, A; Thilaganathan, B; Manzoli, L; Papageorghiou, AT (Wiley, 2016)
Objectives Diagnosis of isolated posterior fossa anomalies in children is biased by the fact that only those that are symptomatic are brought to the attention of the appropriate clinical personnel, and the reported rate is often affected by the adoption of different nomenclature, diagnostic criteria, outcome measures, duration of follow-up and neurodevelopmental tools. The aim of this systematic review was to explore the neurodevelopmental outcome of fetuses with a prenatal diagnosis of isolated posterior fossa anomalies.